Language Minority Education in Croatia: Current Issues and Challenges - Blažević Simić, Ana (Array, 2010)
The Croatian policy for national minorities is based on democratic values developed in relevant United Nations’ instruments for human rights protection, as well as conventions and recommendations of the Council of Europe addressing human rights, which Croatia has ratified. The article provides an overview of those documents but also of domestic legal framework which guarantee the right to education in the language and script of national minorities. In the development of the Croatian education system, national minorities are recognized as a key priority and a target group, and have been offered the specific educational programs in the form of three basic models of education following the standards of efficiency and quality in education. The author considers this minority education policy and analyses its realization level based on recent numerical data, state taken measures and related reports. Considering the overview of previous international reports and recommendations, the author examines the issues of certain segments within the overall education system in detail and suggests possible solutions and challenges for the realization of a more efficient educational process in the language and script of national minorities.